A Review Paper on Indian Education System - SHARMA, DR. MEENAKSHI (The journal of contemporary issues in business and government, 2021)
Indian schooling history have the origin in the ancient times in which Gurukul systems were followed–the systems in which the student lived at their teacher's house unless the Guru or teacher believes that the student has gained everything, he/she can. The topics imparted diverse from Scriptures to Mathematics to Sanskrit and the acquired learning would be imparted down through the generation. Though, during the Colonial period this system was introduced after the Britishers established school that taught a coursework limited to topics like science, maths etc. India's global ranking in education fell to 93 in 2014. This composed by a string of scandals that the Sector of Education in India is experiencing, suggests the urgent requirement to push out changes in our teaching systems. Indian education systems became associated with tests, school exams, entry examinations, markings. Schools have a crucial part to play in influencing the professional and social development of an individual. The Indian traditional schools are based on educating the children to confront the demanding outside environment. We promote tests and assignments as methods for evaluating the students’ performance. Whether or not a child became familiar with the points he / she received. This paper discloses about the changes that education system needs to incorporate.